1995
DOI: 10.1073/pnas.92.10.4279
|View full text |Cite
|
Sign up to set email alerts
|

Replication factor encoded by a putative oncogene, set, associated with myeloid leukemogenesis.

Abstract: DNA replication and transcription of adenovirus (Ad) have been studied extensively as a model eukaryotic system. The dissection and reconstitution of the cell-free DNA replication system using the Ad DNA terminal protein complex (Ad DNAprot) have revealed the detailed mechanism of Ad genome replication (1-3). The Ad genome is a linear DNA of '36 kbp that contains 55-kDa terminal proteins covalently attached to its 5' ends. Replication of the Ad DNA-prot initiates by a protein-priming mechanism in which the 5' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
180
1
4

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(190 citation statements)
references
References 21 publications
5
180
1
4
Order By: Relevance
“…This region of SET contains a large acidic domain that has been described to be involved in a number of functions as for instance, DNA replication of adenovirus genome (Nagata et al, 1995) or cyclin B-cdk1 inhibition (Canela et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This region of SET contains a large acidic domain that has been described to be involved in a number of functions as for instance, DNA replication of adenovirus genome (Nagata et al, 1995) or cyclin B-cdk1 inhibition (Canela et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that nucleosome assembly protein-I (NAP-I) has significant amino acid sequence similarity to TAF-I, and that it can substitute for TAF-I activity in the replication of Ad core DNA (von Lindern et al 1992a;Nagata et al 1995). Nucleosome assembly protein (NAP-I), which contains three negatively charged regions, is found in various eukaryotic cells and has been shown to interact with cellular histones and to facilitate nucleosome formation (Fujii-Nakata et al 1992;Ishimi et al 1987).…”
Section: Substitution For Taf-i By Nap-imentioning
confidence: 99%
“…One protein was identified as non-muscle myosin IIA (NMIIA) and we explored further the possibility that NMIIA may be involved in virus maturation. Here we report on the identity of two of the other VP22-binding proteins as template-activating factor I a and b (TAF-Ia and -b), also named SETa and SETb (Adachi et al, 1994;Nagata et al, 1995;von Lindern et al, 1992). TAF-Ia and -b, identified originally as host factors required for adenovirus core replication, have been implicated in chromatin remodelling and were shown to promote the deposition of histones on naked DNA (Miyaji-Yamaguchi et al, 1999;.…”
Section: Introductionmentioning
confidence: 99%